(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main thrust of this study was to design, make, and assess the acceptability level of the design and development of ecobangku from pressed upcycled plastic sheets with resin called medium density polyethylene (MDPE) boards as the main material of the chair. The study employed the experimental and descriptive research design in the conduct of the study and used a self-made questionnaire to get its acceptability. The data gathered were treated, analyzed and interpreted through the average weighted mean. This was conducted at Bohol Island State University – Main Campus. The questionnaires were distributed in the province of Bohol specifically in the furniture and plastic sheets local firms during the school year 2018-2019 with one hundred forty-five (145) respondents from design experts, design instructors, and end users. It was found out that the design and development of ecobangku from medium density polyethylene boards has an average weighted mean of 3.64 which is described as highly acceptable and interpreted as very high or effective to a great extent. Based from the results, the researcher concluded that the ecobangku using the medium density polyethylene noards is as acceptable as the conventional luxury chair. Thus, the use of upcycled plastic sheets could be applied into different furniture designs..